2020
DOI: 10.1093/bjsw/bcaa079
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Public? An Analysis of Professional Regulation—Comparing Outcomes in Fitness to Practice Proceedings for Social Workers, Nurses and Doctors

Abstract: The regulation of professional activity in the Health and Social Care sector in the UK is carried out by a number of statutory bodies that hold legal mandates to manage the risks of professional malpractice. The prime method used to perform this duty, and thereby protect the public, is the construction of a register of the suitability qualified—and creation of appropriate professional standards to establish a benchmark for practice. When registrant’s performance or conduct is felt not to meet these standards, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…When SWE introduced these rules, it was clear that reform in this area was needed. Research had shown that social workers were more likely to find themselves subject to FtP investigations than other professionals, as well as being more likely to be removed from the register as a result and less likely to be able to engage effectively with the process (Kirkham et al, 2019;Worsley et al, 2020b). However, social work perspectives have once again been marginalised in this process, with no requirement for either case investigators or case managers who are overseeing these investigations to have any experience, or even knowledge, of social work (SWE, 2019a).…”
Section: What Is Social Work England?mentioning
confidence: 99%
“…When SWE introduced these rules, it was clear that reform in this area was needed. Research had shown that social workers were more likely to find themselves subject to FtP investigations than other professionals, as well as being more likely to be removed from the register as a result and less likely to be able to engage effectively with the process (Kirkham et al, 2019;Worsley et al, 2020b). However, social work perspectives have once again been marginalised in this process, with no requirement for either case investigators or case managers who are overseeing these investigations to have any experience, or even knowledge, of social work (SWE, 2019a).…”
Section: What Is Social Work England?mentioning
confidence: 99%
“…These serve to protect the public, but also have the effect of enhancing professionalism 13 by 'asserting professional status'. 14 Codes of conduct and expectations of professional behaviour of nurses are determined by nurse regulators such as the UK Nursing and Midwifery Council and the Irish Bord Altranais. However, Code values are not the only values considered relevant to the recruitment process and there is something of a values' framework tsunami for educators, students and registrants to negotiate.…”
mentioning
confidence: 99%
“…These processes are in keeping with approaches in relation to the fitness to practise of registered nurses. 14 Unlike the approach taken for registered nurses, however, there is little national or international guidance and approaches vary across universities. 16 Anecdotally, there is frustration amongst some educators that for some small numbers of students that face disciplinary hearings or FTP, there is a competition of 'rights' with, at times, the rights of the student appearing to supersede that of the patient.…”
mentioning
confidence: 99%